Human gut microbiota plays a role in the metabolism of drugs - Jourova, Lenka; Anzenbacher, Pavel; Anzenbacherova, Eva (Biomedical papers, 2016)
Background and Aims: The gut microbiome, an aggregate genome of trillions of microorganisms residing in the human gastrointestinal tract, is now known to play a critical role in human health and predisposition to disease. It is also involved in the biotransformation of xenobiotics and several recent studies have shown that the gut microbiota can affect the pharmacokinetics of orally taken drugs with implications for their oral bioavailability.Methods: Review of Pubmed, Web of Science and Science Direct databases for the years 1957-2016.Results and Conclusions: Recent studies make it clear that the human gut microbiota can play a major role in the metabolism of xenobiotics and, the stability and oral bioavailability of drugs. Over the past 50 years, more than 30 drugs have been identified as a substrate for intestinal bacteria. Questions concerning the impact of the gut microbiota on drug metabolism, remain unanswered or only partially answered, namely (i) what are the molecular mechanisms and which bacterial species are involved? (ii) What is the impact of host genotype and environmental factors on the composition and function of the gut microbiota, (iii) To what extent is the composition of the intestinal microbiome stable, transmissible, and resilient to perturbation? (iv) Has past exposure to a given drug any impact on future microbial response, and, if so, for how long? Answering such questions should be an integral part of pharmaceutical research and personalised health care.
Keywords: microbiome; metabolism of drugs; gut microbiota; bioavailability; cytochromes P450